Grape seed proanthocyanidin extracts alleviate oxidative stress and ER stress in skeletal muscle of low‐dose streptozotocin‐ and high‐carbohydrate/high‐fat diet‐induced diabetic rats. Issue 2 (17th November 2012) - Ding, Ye; Dai, Xiaoqian; Jiang, Yanfei; Zhang, Zhaofeng; Bao, Lei; Li, Yujie; Zhang, Feng; Ma, Xiaotao; Cai, Xiaxia; Jing, Lulu; Gu, Jiaojiao; Li, Yong
<x xml:space="preserve">Abstract</x> Although ER stress in pancreas, liver, and adipose tissue was reported to be a novel event linked to the pathogenesis of type 2 diabetes mellitus, there is much less information on this event in skeletal muscle. Some studies indicated that treatment with antioxidants had beneficial effects on ER stress and diabetes. This study focuses on the effects of a strong antioxidant, grape seed proanthocyanidin extracts (GSPE), on skeletal muscle in diabetic rats induced with low dose streptozotocin‐ and a high‐carbohydrate/high‐fat diet. After 16 wk of GSPE treatment, diabetic rats showed decreased plasma glucose levels and insulin resistance. The efficacious effect of GSPE was manifested by the amelioration of muscular damage and dysfunction, as observed by histological examination and periodic acid Schiff staining. Concurrently, calcium overload and the abnormal activities of antioxidant enzymes and ATPases in diabetic muscles were partially reversed by GSPE treatment. GSPE also increased the activity of protein kinase B (a mediator of insulin's metabolic action) and partially alleviated severe ER stress. These findings suggest that GSPE may have auxiliary therapeutic potential for type 2 diabetes mellitus by decreasing oxidative stress and ER stress in skeletal muscle.